The age and tectonic status of the Revseggi Nappe, southwestern Norway - Ringstad, Håkon Blaker (2019)
The Hardangervidda – Ryfylke Nappe Complex is a dominant element in the southwestern segment of the Norwegian Caledonides. The section in Røldal includes a Proterozoic basement, with the following over-thrusted allochthonous units; the Holmasjø Nappe (Ordovician), the Dyrskard and Kvitenut nappes (both Mesoproterozoic) and on top the Revseggi Nappe (Neoproterozoic or Cambrian). The Revseggi Nappe is the uppermost tectonic unit in its area and consists largely of metasedimentary rocks with intercalated lens-shaped metaintrusive rocks and pegmatites. The Nappe is strongly sheared, and ductile deformation indicates top to the ESE as the main transport direction following the regional Caledonian orogenic movement. Strain partition is present and expressed by an upward decrease in deformation intensity and the development of several intrinsic thrust faults. The nappe has gone through several tectonic stages and new data obtained by U-Pb ID-TIMS dating of zircon, titanite and rutile suggests a Late Cambrian bimodal intrusive event at 494,5 ± 1,6 Ma and multiple metamorphic phases both in the Ordovician at 450,4 ± 0,8 Ma and in the Silurian at 437,2 ± 0,8 Ma. The latter event was closely related to the emplacement of the Revseggi Nappe onto the Kvitenut Nappe and the initiation of the Scandian Orogeny. Further work should be done to investigate the possible links between the Revseggi Nappe, the Karmøy and the Bømlo ophiolites, and the bimodal magmatism at the Laurentian side (Newfoundland and Nova Scotia) which expresses syn-magmatic activity during Late Cambrian. These connections could possibly indicate that the Revseggi Nappe is of Laurentian affinity rather than Baltican. The Revseggi and the Jæren nappes show also similarities in lithological compositions and tectonometamorphic history. Though the Jæren Nappe also comprises eclogites, the two nappes went through metamorphism at amphibolite facies conditions and might be a part of the same system.